AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN WRITING (A CASE STUDY AT THE XI BAHASA CLASS OF SMA NEGERI 4 KOTA BENGKULU) - Revvi Ayu Fratiwi; Kasmaini Kasmaini; Ildi Kurniawan (Journal Cerdas Mahasiswa, 2022)
The research aimed to find out the students’ difficulties in writing at XI Bahasa Class of SMA Negeri 4 Kota Bengkulu. The type of research was qualitative research. There were 32 students at the XI Bahasa Class of SMA Negeri 4 Kota Bengkulu in academic year 2020/2021 as the subject of the research. Instruments of this research were writing test and interview. The results of the test was analyzed with assessment criterion tell by Heaton (1988). The result of the research found that students’ difficulties in writing from five components (content, organization, vocabulary, language use and mechanics) at the XI Bahasa Class of SMA Negeri 4 Kota Bengkulu were content and language use. The students’ writing was average. Based on the table criterion in research finding, 16 students in average category, 11 students in very good category, 4 students in poor category, and 1 students in very poor category.